Pattern recognition receptor CD14 gene polymorphisms in alcohol use disorder patients and its Influence on liver disease susceptibility - Roy, Neelanjana; Nadda, Neeti; Kumar, Hem; Prasad, Chandreswar; Kumar Jha, Jyotish; Pandey, Hem Chandra; Vanamail, Perumal; Saraya, Anoop; Balhara, Yatan Pal Singh; Shalimar; Nayak, Baibaswata (Frontiers in Immunology, 2022)
Background: Alcohol use disorders (AUD) leading to liver disease is major concern over other spectrum of disorder. Excessive alcohol consumption resulting in leaky gut syndrome is attributed to alcohol-induced liver injury through portal translocation of bacterial endotoxin. Susceptibility to alcoholic liver disease (ALD) in AUD patients could be dependent upon genes responsible for inflammation and alcohol metabolism. The pattern recognition receptor CD14 gene is a major player of endotoxin-mediated inflammation and susceptibility to ALD. Genetic association of CD14 polymorphisms and other mechanisms relevant to altered inflammatory responses leading to ALD was investigated in this study. Methods: Patients of alcohol use disorder with ALD (n=128) and without liver disease (ALC, n=184) and controls without alcohol use disorder (NALC, n=152) from North India were enrolled. The CD4 gene polymorphisms in north Indian population were evaluated by RFLP and sequencing. Secretory CD14 (sCD14), LBP, TLR4, MD2, TNFα, IL1b, IFNγ, IL6, IL10 and IL4 levels in serum were measured by ELISA among groups. Influence of polymorphisms on CD14 gene promoter activity and circulatory bacterial DNA level were determined. Results: The CD14 gene promoter and exonic region SNPs were found monomorphic except SNP rs2569190 for north Indian population. The genetic association of SNP rs2569190(C/T) with risk of developing ALD was found significant for TT genotype [ORTT, 95% CI =2.19, 1.16-4.13 for ALD vs. ALC and OR, 2.09, 1.18-3.72 for ALD vs. NALC]. Increased sCD14 level was observed in AUD patients than NALC control. Increased levels of LBP, TLR4, TNFα, IL1β, IFNγ and IL6 and reduced levels of MD2, IL10 and IL4 were observed among the ALD patients than the other two control groups. Elevated levels of the pro-inflammatory and reduced levels of anti-inflammatory cytokines were observed in risk genotype TT groups of ALD patients and ALC group than NALC. Promoter activity was observed in the intronic region flanking SNPs and risk genotype can influence reporter activity indicating CD14 gene expression. Conclusion: Enhanced CD14 expression associated with inflammatory responses increases susceptibility to ALD in TT genotype of AUD patients.